2020
DOI: 10.30585/jrems.v2i2.465
|View full text |Cite
|
Sign up to set email alerts
|

Financial flexibility, dynamic capabilities, and the performance of manufacturing enterprises

Abstract: This study explores the mechanism of financial flexibility on enterprise performance from the perspective of dynamic capabilities by testing the relationship among them respectively. This study selects the data of A-share manufacturing companies in Shenzhen and Shanghai from 2011 to 2017 to structure three main variables mentioned above. The test results of the regression analysis indicate that financial flexibility has an interval effect on enterprise performance. Dynamic capabilities play a part in mediating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 23 publications
(28 reference statements)
1
16
2
Order By: Relevance
“…Studies on the FF-EP relationship have found it to be either positive (Al-Slehat, 2019;Arslan-Ayaydin et al, 2014;Ma and Jin, 2016), negative (Agha and Faff, 2014) or an inverted U-shape (Gu and Yuan, 2020;Yi, 2020). However, this research found the FF-EP relationship to be U-shaped in the hospitality industry amid the COVID-19 shock.…”
Section: Theoretical Implicationscontrasting
confidence: 55%
See 3 more Smart Citations
“…Studies on the FF-EP relationship have found it to be either positive (Al-Slehat, 2019;Arslan-Ayaydin et al, 2014;Ma and Jin, 2016), negative (Agha and Faff, 2014) or an inverted U-shape (Gu and Yuan, 2020;Yi, 2020). However, this research found the FF-EP relationship to be U-shaped in the hospitality industry amid the COVID-19 shock.…”
Section: Theoretical Implicationscontrasting
confidence: 55%
“…2. Literature review and hypotheses development FF refers to an enterprise's ability to access and restructure its financing at low costs (Gamba and Triantis, 2008), seize investment opportunities, acquire and invoke resources and maximize its value and resiliency during unexpected events (Graham and Harvey, 2001;Ma and Jin, 2016;Yi, 2020). FF is essential to an enterprise's financial decision-making, as it assists with selecting profitable investments and maintaining debt and future financing capacity (Marchica and Mura, 2010).…”
Section: Ijchm 342mentioning
confidence: 99%
See 2 more Smart Citations
“…Definition and measure of financial flexibility FF can be defined as "an enterprise's ability to access funds to finance positive net present value projects and to withstand financial risk" (Bonaimé et al, 2014;Ferrando et al, 2017). To be more specific, FF is the "ability of a firm to effect resilience when faced with unexpected events or crises, timely acquire or invoke resources, seize opportunities to invest" (Bates et al, 2009;Cherkasova & Kuzmin, 2018;DeAngelo et al, 2011;Denis & Mckeon, 2012;Graham & Harvey, 2001;He et al, 2020;Ma & Jin, 2016;Opler et al, 1999;Yi, 2020;Zhang et al, 2020). FF plays a vital role in the financial decision-making of enterprises.…”
Section: Theory Of Capital Structurementioning
confidence: 99%